Structural analysis of the hip joint using segmentation and finite elements in patients with femoroacetabular impingement - Castillo, Felipe; Hernández-Salazar, Cristian A.; González-Estrada, Octavio A. (Frontiers in Mechanical Engineering, 2025)
Musculoskeletal disorders pose a significant challenge due to their profound impact on mobility and quality of life. Among these, cam-type femoroacetabular impingement stands out for its effect on femoral head morphology, causing joint pain and limiting movement. This study explores the biomechanical consequences of cam-type impingement through comprehensive analysis using computed tomography (CT) scans. Advanced 3D segmentation performed with 3D Slicer software enabled precise three-dimensional hip joint models. Mechanical properties, including Young’s modulus and density, were directly derived from CT data and integrated into finite element models developed in Ansys. The simulations assessed the hip joint’s response during flexion and abduction, replicating dynamic conditions commonly encountered in daily activities. Results demonstrated that cam-type impingement leads to elevated stress concentrations and altered contact patterns. Abduction generated the highest strain values, reaching 0.0578 mm/mm, while flexion induced greater relative changes, with up to a 22.72% variation between healthy and affected joints. These findings provide critical insights into joint mechanics under pathological conditions, underscoring the potential of biomechanical modeling for enhancing diagnostic accuracy and therapeutic interventions. By identifying stress concentration zones, the study highlights the utility of finite element models in designing improved surgical techniques and targeted rehabilitation protocols, ultimately advancing treatment outcomes for patients with femoroacetabular impingement.